LncRNA HCG11 Facilitates Nasopharyngeal Carcinoma Progression Through Regulating miRNA-490-3p/MAP3K9 Axis - Zheng, Jian; Zhao, Zhuochen; Ren, Huijun; Wang, Yongfeng; Meng, Xianchun; Zhang, Wenjing; Zhang, Cai; Ming, Liang; Lu, Xiubo (Frontiers in Oncology, 2022)
Purpose: Long noncodingRNAs (LncRNAs) play complex but important roles in the progression of various tumors. This studyaimed to elucidate the functional mechanisms of the HLA complex group 11 (HCG11) in nasopharyngeal carcinoma (NPC). Patients and methods:HCG11levelsin NPC specimens were determined by fluorescence in situ hybridization (FISH) and qPCR. Proliferation, apoptosis, and metastasis of NPC cells were determined usingCCK8, colony formation, annexin V-PI, and transwellassays. A murine tumor xenograft model was used to investigate the regulatory function of HCG11 in NPC in vivo, and immunohistochemical staining was used to determinethe Ki-67 level in tumors. The target relationships between HCG11, microRNA miR-490-3p, and MAPK kinase kinase 9 (MAP3K9) were detected using bioinformatics, qPCR, western blotting, and luciferase reporter assays. Results:HCG11 was highly expressed in NPC tissuesand was positively associated with tumor stage, lymphatic metastasis, and poor prognosis. Functionally, HCG11 knockdown inhibitedproliferation and migration and induced apoptosis of NPC cells. Mechanistically, miR-490-3p is a direct target of HCG11, oncogenic functions of HCG11 in NPC cell proliferation and migration canbe partially reversed by the miR-490-3p inhibitor. HCG11 significantly increasedmitogen-activated protein kinase MAPK kinase 9 (MAP3K9) levelsbyinhibitingmiR-490-3p. Conclusion: HCG11 facilitates NPC progression via MAP3K9 signaling by sponging miRNA-490-3p, which may contribute to new prognostic markers andpromising therapeutic targets.